Clenbuterol Attenuates hERG Channel by Promoting the Mature Channel Degradation. (July 2017) - Luo, Ling; Hu, Peijing; Miao, Changqing; Ma, Aiqun; Wang, Tingzhong
Clenbuterol, a β2-selective adrenergic receptor agonist, is illicitly used in weight loss and performance enhancement and animal production. Increasing evidence demonstrates that clenbuterol induces various kinds of arrhythmias and QTc interval prolongation. However, little is known about the underlying mechanism. Most drugs are associated with QTc prolongation through interfering with human ether-a-go-go-related gene (hERG) K + channels. The present study aims to investigate the effects and underlying mechanisms of clenbuterol on the hERG channel. HEK 293 cells were transfected with wild type and Y652A or F656A mutants of the hERG channel and treated with clenbuterol. The hERG current was recorded using whole-cell patch-clamp technique, and protein level was evaluated by Western blot. We found that clenbuterol decreases the mature form of the hERG protein at the cell membrane in a concentration- and time-dependent manner, without affecting the immature form. Correspondingly, clenbuterol chronic treatment reduced hERG current to a greater extent compared to acute treatment. In the presence of Brefeldin A (BFA), which was used to block hERG channel trafficking to cell membrane, clenbuterol reduced hERG on plasma membrane to a greater extent than BFA alone. In addition, the hERG channel's drug binding sites mutant Y652A and F656A abolished clenbuterol-mediated hERG reduction and current blockade. In conclusion, clenbuterol reduces hERG channel expression and current by promoting the channel degradation. The effect of clenbuterol on the hERG channel is related to the drug-binding sites, Tyr-652 and Phe-656, located on the S6 domain. This biophysical mechanism may underlie clenbuterol-induced QTc prolongation or arrhythmia.